An aggregate theory of international payments adjustment - Gray, H. Peter (Lexington, Mass.: Lexington Books, 1974)
As the title implies, this book is attempting to integrate long term capital flows both direct and portfolio-into international economic adjustment analysis. It noted that the accepted equilibrium adjustment explanation is really a trade adjustment theory. The model presented is designed to liberate balance-of-payments theory from the general equilibrium framework in which it has been confined.
Includes index
Includes bibliographical references.
usc 30/4/18
Loans
Keywords: Balance of payments